COVID 19 y su impacto en las finanzas PYMES textileras del cantón Riobamba 2020 - 2021. - Tapuy Alvarado, Rody Andrés (2023)
COVID 19 and its impact on the finances of textile SMEs of the Riobamba canton 2020-2021 PYMES within the economy of Ecuador have become fundamental, since its inception they have generated jobs, after the COVID 19 pandemic has caused a crisis that is already a reality in Latin America, the main challenges that the financial impact on companies had from Ecuador were the work groups in quarantine, irregularities in supplies, loss in inventories or drops in demand for products and services, for this reason the present investigation had the objective of analyzing COVID 19 and its impact on the finances of textile PYMES of the Riobamba canton 2020–2021. The methodology had a quantitative approach based on descriptive and bibliographical research, we worked with a population made up of 4 industrial textile companies from the Riobamba canton, whose legal situation is active, where a survey was applied in order to gather information with the purpose of to know the impact that COVID-19 had on the finances of textile PYMES in the Riobamba canton. As results, it was evidenced that the companies presented a negative affectation due to the pause in the activities they carried out, since the lack of raw material has been the main obstacle that the textile companies had to produce and deliver their merchandise. Finally, it is concluded by indicating that most of the textile companies had serious effects not only in the economic part but also with respect to their workforce, since they did not have an adequate contingency plan that would allow companies to prevent this type of crisis beforehand.